A cohort study of wastewater treatment plant workers: Association between levels of biomarkers of systemic inflammation and exposure to bacteria and fungi, and endotoxin as measured using two methods. (1st March 2023) - Madsen, Anne Mette; Uhrbrand, Katrine; Kofoed, Victor Carp; Fischer, Thea K.; Frederiksen, Margit W.
Highlights: A cohort study of wastewater workers' exposure and systemic inflammation. The Limulus and rFC endotoxin assays showed different exposures levels. Inflammation was associated positively with Limulus and rFC endotoxin exposure. Inflammation was associated positively with Limulus and rFC endotoxin dose. Risk class 2 and allergenic fungi were present in workers' exposure. Abstract: Work in wastewater treatment plants (WWTPs) can be associated with exposure to airborne microorganisms and endotoxin from the working environment. The aim of this study was to obtain knowledge about whether serum levels of the markers of systemic inflammation, C-reactive protein (CRP) and serum amyloid A (SAA), are associated with personal exposure to endotoxin, measured using the Limulus (endotoxinLimulus ) and the rFC (endotoxinrFC ) assays, as well as bacteria and fungi in a cohort of WWTP workers. Exposure and blood samples were collected for 11 workers over one year. Exposure to endotoxinLimulus-day and endotoxinrFC-day correlated significantly ( r  = 0.80, p <0.0001, n  = 104), but endotoxinLimulus-day was 4.4 (Geometric mean (GM) value) times higher than endotoxinrFC-day ( p <0.0001). The endotoxinLimulus-day, endotoxinrFC-day, bacteria, and fungal exposure as well as serum levels of CRP-day (GM=1.4 mg/l) and SAA-day (GM=12 mg/l) differed between workers. Serum levels of SAAday correlated significantly with CRPday ( r  = 0.30, p  = 0.0068). The serum levels of CRPday were associated significantly with exposure to endotoxinLimulus-day . Exposure, SAA and CRP data were also analyzed as av. of each season, and SAAseason was associated positively and significantly with endotoxinLimulus-season and endotoxinrFC-season and negatively with fungalseason exposure. In conclusion, CRPday was associated with the endotoxinLimulus-day and SAAseason with endotoxinLimulus-season and endotoxinrFC-season exposure. Thus, we hereby document that WWTP workers are exposed to airborne endotoxin which seems to have a negative impact on their health. Graphical abstract: Image, graphical abstract